Natural Competence Is Common among Clinical Isolates of Veillonella parvula and Is Useful for Genetic Manipulation of This Key Member of the Oral Microbiome - Knapp, Steven; Brodal, Clint; Peterson, John; Qi, Fengxia; Kreth, Jens; Merritt, Justin (Frontiers in Cellular and Infection Microbiology, 2017)
The six Veillonella species found in the human oral cavity are among the most abundant members of the oral flora, occurring in both supra- and subgingival dental plaque as well as on the oral mucosa. Epidemiological data have also implicated these species in the development of the most common oral diseases. Despite their ubiquity, abundance, and ecological significance, surprisingly little is known about Veillonella biology, largely due to the difficulties associated with their genetic manipulation. In an effort to improve genetic analyses of Veillonella species, we isolated a collection of veillonellae from clinical plaque samples and screened for natural competence using a newly developed transformation protocol. Numerous strains of V. parvula were found to exhibit a natural competence ability that was highly influenced by growth medium composition. By exploiting this ability, we were able to utilize cloning-independent allelic exchange mutagenesis to identify the likely source of DNA uptake machinery within a locus homologous to type II secretion systems (T2SS). Interestingly, V. parvula natural competence was found to exhibit a clear hierarchy of preference for different sources of DNA (plasmid < PCR product < genomic DNA), which is unlike most naturally competent species. Genomic comparisons with other members of the Veillonellaceae family suggest that natural competence is likely to be widely distributed within this group. To the best of our knowledge, this study is the first demonstration of natural competence and targeted allelic exchange mutagenesis within the entire Veillonellaceae family and demonstrates a simple and rapid method to study Veillonella genetics.